Transforming Plastic Waste Into Ecobricks For Park Revitalization And Environmental Education - Dony Novaliendry; Riani; Rahmadina Oktarina; Azraril Azizah; Gladis Aprilia Rahayu; Humaira Khairunnisa; Aliman; Muhammad Figli Fajar (Jurnal Pengabdian Masyarakat, 2026)
Purpose: This study addresses severe plastic waste accumulation degrading public park aesthetics by transforming waste into ecobricks for space revitalization and environmental education. Method: A one-month community program (June–July 2025) utilized waste counseling, hands-on ecobrick training, collaborative production, and educational board installation, documented through field observations and photography. Practical Applications: The ecobrick model provides a low-cost, scalable waste management strategy for municipalities, fostering community cooperation while delivering accessible environmental education tools for schools and public areas. Conclusion: Producing 80 ecobricks created a park icon and informational displays, significantly improving park cleanliness and public awareness. This confirms ecobricks as a sustainable, community-driven solution for plastic waste reduction and environmental stewardship.